Chemical Examination of Bark of Terminalia paniculata Roth - Beri, R. M.; Karnik, M. G. (Indian Forester, 1965)
Analyses of Teminalia paniculata Bark shows that it is made up to 27 per cent of extractives that can be removed by slIccessive extraction with petroleum ether, ch1oroform, alcohol and water, 28 per cent of carbohydrate, 33 per cent of 'lignin' and 9.6 per cent of ash. The bark does not contain any alkaloids. It contain. 14 per cent of tannins, which have a pyrogallol nucleus in the molecule rather than a catechol nucleus along with gallic acid . Î²-sitosterol has been isolated and identified from the petroleum ether extract of the bark.